The Role of Land Deed Officials in Preventing the Issuance of Duplicate Certificates (Case Study on Court Decision Number 02/PDT.G/2013/PN.ADL) - Zhona Washilatul Khasanah; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the role of the Land Deed Official (PPAT) in preventing the issuance of double certificates, with a case study on Court Decision Number 02/PDT.G/2013/PN.ADL. The background of this research is based on the high number of land disputes in Indonesia caused by the issuance of double certificates. Double certificates create legal uncertainty and can harm various parties. PPAT plays a strategic role in ensuring the validity of documents and the legality of each land transaction to avoid such issues. This research uses a normative juridical method with a descriptive-analytical approach. Data were obtained from literature studies involving relevant laws and regulations, such as Law Number 5 of 1960 concerning Basic Agrarian Principles and Government Regulation Number 24 of 1997 concerning Land Registration. In addition, court decisions were analyzed to understand the dynamics of PPAT's role in preventing double certificates. The results show that PPAT plays an important role in verifying documents, ensuring the validity of land ownership data, and preventing duplicate certificates through coordination with the National Land Agency (BPN). However, challenges such as limited access to remain accurate land data and weak internal supervision obstacles. It is necessary to improve PPAT's competence and strengthen the land administration system to minimize the risk of double certificate issuance in the future.